Manufacturing crisis under globalisation: middle-class precarity in Dave Eggers's A Hologram for the King. Issue 5 (4th May 2022) - Varsava, Jerry
ABSTRACT: Large swaths of homo economicus americanus today confront chronic unemployment or under-employment in a period of tremendous offshoring of the production of goods and services, high consumer debt, static or declining disposable incomes, and shrinking governmental supports, even as large income gains and increasing wealth concentration are enjoyed by the rich and hyper-rich. In recent years, Dave Eggers has authored a number of post-postmodern novels that address the divergent trajectories of various contemporary American economic actors. This essay investigates one of these works, A Hologram for the King (2012), which details the long decline of the American manufacturing sector since the late seventies through globalisation, and the angst and material suffering of downward economic mobility that this has occasioned. Through qualitative and quantitative analyses, this essay examines Hologram 's depiction of middle-class precarity and its repudiation of American exceptionalism, as well as its anticipation of the Trump Administration's global trade wars. Finally, in its conclusion, the essay takes up philosophical and political issues related to economic globalisation in contemporary American and global society.